Concordance of PD‐L1 expression in matched urothelial bladder cancer specimens. Issue 6 (25th September 2018) - de Jong, Joep J; Stoop, Hans; Nieboer, Daan; Boormans, Joost L; van Leenders, Geert J L H
Abstract : Aims: Programmed death ligand 1 (PD‐L1) expression has predictive value for response to immune‐checkpoint inhibitor treatment in urothelial cancer patients. The consistency of PD‐L1 expression among different specimen types, however, is unknown. The aim of this study is to compare PD‐L1 expression in matched transurethral resections of the bladder (TURB), cystectomy specimens and lymph node metastases of urothelial cancer patients. Methods and results: We performed PD‐L1 (SP142) immunohistochemistry on whole tissue slides of 115 urothelial carcinoma patients who had undergone TURB, followed by radical cystectomy and/or pelvic lymph node dissection. The PD‐L1 assay was positive if PD‐L1 expression in immune cells occupied ≥5% of the tumour area. PD‐L1 was positive in 15 of 97 (15.5%) TURB, 17 of 98 (17.3%) cystectomies and nine of 49 (18.4%) lymph node metastases. Agreement of PD‐L1 assay outcome between cystectomy and TURB (kappa = 0.34; P = 0.002) and cystectomy and lymph node metastasis (kappa = 0.35; P = 0.034) was fair; there was no agreement between TURB and lymph node metastasis (kappa = 0.045; P = 0.82). Discordance of PD‐L1 outcome in matched TURB and cystectomy specimens occurred more frequently after neoadjuvant therapy (53.3% versus 25.4%; P = 0.03), and was not associated with other clinicopathological parameters. Conclusions: Urothelial bladder cancer patients showed fair agreement of PD‐L1 assay outcome in cystectomies and matched TURB or lymph node specimens. PD‐L1 expression was discordant more often after neoadjuvant therapy. Therefore, immune‐checkpoint inhibitor studies should take into account specimen type and neoadjuvant therapy in assessing the predictive value of PD‐L1 expression.